EFEKTIVITAS HUKUM PENDAFTARAN MEREK DI KALANGAN PENGUSAHA KECIL DAN MENENGAH BATIK DI PUSAT GROSIR SOLO - Inneke Saphira Soesanto; Diana Tantri C (Fakultas Hukum Universitas Sebelas Maret, 2023)
This article aims to find out about the obstacles of implementing brand registration among small and medium batik entrepreneurs in Pusat Grosir Solo and solutions to the obstacles of implementing brand registration among small and medium batik entrepreneurs in Pusat Grosir Solo. Empirical legal research is descriptive with the research site at the Pusat Grosir Solo. The types and sources of this research data include primary and secondary data. Data collection techniques with interviews and literature studies. The data analysis technique is qualitatively. The results tells that the barriers to the implementation of brand registration among small and medium-sized batik entrepreneurs in Pusat Grosir Solo are divided into two, namely non-normative barriers and normative barriers. Non normative barriers are a lack of understanding about the brand and its registration, limited funds owned by SMEs, and concerns about the brand being not accepted for registration due to similarities to existing brands. Then there are normative obstacles is brand registration arrangements as stipulated in Article 14 paragraph (1), Article 14 paragraph (2), and Article 23 paragraph (5) of Law No. 20 of 2016 concerning Brands and Geographical Indications take a long time (8 months). The solution to non-normative barriers is to empower SMEs regarding the brand and its registration conducted by the Surakarta City Government, the issuance of SME recommendation letters by Disnakerperin and Dinkop SME so that registration costs are cheaper, and to address concerns about brands not being accepted for registration due to similarities to existing brands, may register the brand collectively. For solutions to normative barriers, there needs to be a revision of Law No. 20 of 2016 on Brands and Geographical Indications related to the process of brand registration to be shorter.